CALENDERIAL RITUAL SYAWALAN SEBAGAI MEDIASI â€œNGALAP BERKAHâ€ MASYARAKAT KALIWUNGU KENDAL - YANTO, HADI (HUMANIKA, 2013)
ABSTRACT Syawalan is a religious ceremony system in Javanese culture that has been a tradition to date carried out by traditional Muslim communities in Kaliwungu Kendal Regency in particular. This paper discusses the history, pattern, essence, meaning, and function of Syawalan as calenderial ritual tradition that has lasted decades. Syawalan as mediation "ngalap berkah" to the Auliyaâ€™ (Saint) or the cultural heroes, that is so dear to the hearts of the people and communities so that they are believed to have many "kekuatan karamahâ€ during his lifetime because of the sanctity of life and the value of the quality of piety to God. Keywords: calenderial ritual syawalan, cultural heroes, ngalap berkah